![\begin{gathered} \text{ Given} \\ 4x^2+12x=-12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qkviw3wuo7khmj47twszjr7m2z2357zyyz.png)
First, equate the given to zero, and determine its coefficients a,b, and c
![\begin{gathered} 4x^2+12x=-12 \\ 4x^2+12x+12=-12+12 \\ 4x^2+12x+12=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1bh2j4wxnnicvgqdadwy6ik102zo079top.png)
It is now in the standard form where a = 4, b = 12, and c = 12. Substitute these values to the quadratic formula and we get the following
![\begin{gathered} x = ( -b \pm √(b^2 - 4ac))/( 2a ) \\ x = ( -12 \pm √(12^2 - 4(4)(12)))/( 2(4) ) \\ x = ( -12 \pm √(144 - 192))/( 8 ) \\ x = ( -12 \pm √(-48))/( 8 ) \\ x = ( -12 \pm 4√(3)\, i)/( 8 ) \\ \; \\ x_1=( -12 )/( 8 )+(4√(3)\, i)/( 8 ) \\ x_1=-( 3)/( 2 )\pm( √(3)\, i)/( 2 ) \\ \; \\ x_2=( -12 )/( 8 )-(4√(3)\, i)/( 8 ) \\ x_2=-( 3)/( 2 )-( √(3)\, i)/( 2 ) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/accpkjsv5261g0awnh8ovw6459pmfuv7o9.png)
Therefore, the solution to the equation is
![\begin{gathered} x=-( 3)/( 2 )+( √(3)\, i)/( 2 ) \\ \text{ and} \\ x=-( 3)/( 2 )-( √(3)\, i)/( 2 ) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cy4mrh14wxdqonytlymb9wraajx7yv8wmk.png)